English teachers' language skills: possible problems in the implementation of the Malaysian language policy - Mat Daud, Nuraihan; Mat Daud, Nor Shidrah; Md Zamin, Ainul Azmin (IIUM Press, International Islamic University Malaysia, 2011)
Malaysia is a country which has experienced a number of changes in her language policy. Most of the time, the tussle is between the national language,Bahasa Melayu, and the second language, English. The latest change involves reverting to the use of Bahasa Melayu in the teaching of Science and Mathematics at school. This means that English teachers will be expected to play bigger role in improving students' English language proficiency. To make this possible, it is imperative that teachers are highly proficient in the language.Experience shows that this is not necessarily the case. This paper discusses the current state of affairs where English language teaching is concerned. The problem is highlighted by taking the essays produced by applicants for English language teaching posts at a public university in Malaysia from the year 2008 until June 2010 as a case study. A written test was part of the interview process at the university. Only the papers of Malaysians who went through the Malaysian system of education were analysed for this study. This was to assess their writing ability. The analysis shows that many of them did not have the expected level of proficiency although they majored in English or TESL/TESOL. Various errors were detected. The highest number of error was in sentence structure. This was followed by subject-verb agreement,mechanics of writing,vocabulary, word-form, article, prepositions, tense marking,fragments and use of pronouns.